Fluid flow monitoring in oilfields using downhole measurements of electrokinetic potential - saunders,J; jackson,M; pain,C (Geophysics, 2008)
Downhole measurements of electrokinetic potential are a promising new technology for hydrocarbon reservoir monitoring. Using a 3Dfinite-element model combining both multiphase flow and electrokinetic components, we investigated the behavior of electrokinetic (streaming) potential during oil production in a range of reservoir environments. We found that streaming-potential signals originate at fluid fronts and at geologic boundaries where fluid saturation changes. As water encroaches on an oil production well, the streaming-potential signal associated with the water front encompasses the well even when the front is up to 100 m away, so the potential measured at the well starts to change significantly relative to a distant reference electrode. Variations in the geometry of the encroaching water front can be characterized using an array of electrodes positioned along the well, but a good understanding of the local reservoir geology is required to identify signals caused by the front. The streaming potential measured at a well is maximized in low-permeability reservoirs produced at a high rate and in thick reservoirs with low shale content. However, considerable uncertainties remain, particularly relating to the nature of electrokinetic coupling at high salinity and during multiphase flow. Our results suggest that the streaming potential at low salinity (10^-3–10^-4 mol/L) is large (100–1000 mV) but might become too small to resolve (<0.1) mV at high salinity (0.5–2 mol/L), depending on how the available data for the electrokinetic coupling at low salinity are extrapolated into the high-salinity domain. More work remains to determine the behavior of electrokinetic coupling and therefore the utility of this technique at high salinity.